(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article is devoted to the study of the issues of somatometric indicators that form the basis for assessing the physical development of children, since it is in any age period that it reveals the dialectic of the relationship between the body and the environment, characterizes the metabolic processes in the body and its functional state.